Lofty ambitions, new territories and turf battles: China’s platforms ‘go out’ - Keane, Michael; Wu, Huan (2018)
This article surveys the internationalization of China’s leading digital communication and entertainment companies, Baidu, Alibaba, and Tencent, and their strategic acquisitions, both domestic and international. The article shows that with regard to audiences and users of their platforms, the most likely “take-off” points outside the Mainland are within Asia. Future prospects for expansion include the One Belt One Road region (the old Silk Road including central Asia), where state-owned enterprises are currently laying out infrastructure. Acquisitions serve a dual purpose: they establish beachheads for expansion overseas, and they allow foreign media to “send” their content to China. The article notes three levels of “going out”: cultural products and services, ideology, and organizations. The article compares the official state cultural media apparatus to the maritime hero Zheng He in the early Ming dynasty, who took a message of cultural supremacy from the center (i.e. the Middle Kingdom) to the peripheral regions. However, the new media companies and their platforms are not representing the government; they are consolidating their operations and aggregating audiences. The article asks, “Whose interests are ultimately being served?”